THE HISTORICAL AND CULTURAL BACKGROUND OF POLITICAL COMMUNICATION IN ROMANIA / DER ZEITHISTORISCHE UND KULTURELLE HINTERGRUND DER POLITISCHEN KOMMUNIKATION IN RUMÄNIEN - STEGHERR, Marc (Studia Universitatis Babes-Bolyai Studia Europaea, 2016)
The media in Western (and Eastern) Europe are in a serious crisis. The gap between published and public opinion is steadily widening. The crisis of Romanian transformation policy and political communication is reflected in a media crisis and more generally in a crisis of trust in political institutions. The disappointment with sluggish political and social change is growing. The article describes the political, social, cultural and intellectual background and the problems of the present Romanian political and public discourse. The main reason why since the end of communist dictatorship, no fundamental change towards an open and impartial discourse could be achieved is seen in the persisting deficits of democratic transformation and political communication.